Management of Pancreatic Cancer: Current Status and Future Directions - Ramesh, H. (Springer-Verlag, 2010)
Pancreatic ductal adenocarcinoma has a dismal prognosis, despite advances in surgery, and adjuvant therapy. Surgical resection with negative margins remains the mainstay of treatment, and results can be improved with neoadjuvant therapy when the lesion is of borderline respectability. Extended lymphadenectomy has no role in improving survival, but may worsen quality of life. Venous resection can be performed if it helps to achieve an R0 resection, but arterial resection is not justified. A host of newer agents, both cytotoxic and targeted, are being evaluated. The article summarizes the critical issues and looks ahead to the future.